2018
DOI: 10.1017/sjp.2018.3
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Growth Reading Patterns for at-Risk Spanish-Monolingual Children as a Function of a Tier 2 Intervention

Abstract: The present study compares the patterns of growth of beginning reading skills (i.e., phonemic awareness, phonics, fluency, vocabulary and comprehension) of Spanish speaking monolingual students who received a Tier 2 reading intervention with students who did not receive the intervention. All the students in grades K-2 were screened at the beginning of the year to confirm their risk status. A quasi-experimental longitudinal design was used: the treatment group received a supplemental program in small groups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…A systematic review of less extensive, Tier 2 type interventions at the early elementary level (kindergarten through 3 rd grade) has been conducted demonstrating positive effects on both standardized and non-standardized measures of foundational reading skills, and standardized measures of language/comprehension (Wanzek et al, 2016). Nevertheless, there are fewer studies in a monolingual Spanish-speaking population (Crespo et al, 2018;Jiménez et al, 2010). Jiménez et al (2010) conducted a pilot study examining the effectiveness of the Program for the Prevention of Specific Learning Difficulties in Reading ([PREDEA] by its acronym in Spanish) in grades K-2.…”
Section: Implementing Rti Tier 2 In the Spanish Languagementioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of less extensive, Tier 2 type interventions at the early elementary level (kindergarten through 3 rd grade) has been conducted demonstrating positive effects on both standardized and non-standardized measures of foundational reading skills, and standardized measures of language/comprehension (Wanzek et al, 2016). Nevertheless, there are fewer studies in a monolingual Spanish-speaking population (Crespo et al, 2018;Jiménez et al, 2010). Jiménez et al (2010) conducted a pilot study examining the effectiveness of the Program for the Prevention of Specific Learning Difficulties in Reading ([PREDEA] by its acronym in Spanish) in grades K-2.…”
Section: Implementing Rti Tier 2 In the Spanish Languagementioning
confidence: 99%
“…However, the source of variation due to school was not taken into account in this study. In a second study, Crespo et al (2018) analyzed the effects of PREDEA by comparing the growth of students using the Hierarchical Linear Modeling (HLM), controlling the variability due to the subject (2 nd level of the HLM) and school (3 rd level of the HLM). The authors found significant differences between the experimental group and the control group in vocabulary tasks in kindergarten, and in phonological awareness tasks in kindergarten and 1 st grade.…”
Section: Implementing Rti Tier 2 In the Spanish Languagementioning
confidence: 99%
“…With the RTI approach, students are provided with evidence-based classroom reading instruction and supplemental intervention when needed; intervention decisions are based on student assessment data [ 18 ]. Even though there is major support for the RTI approach [ 7 , 18 ], it continues to be poorly implemented in Spain [ 19 , 20 ]. Recently, a study performed in the Canary Islands has shown the effectiveness of RTI in early identification and remediation of reading and math difficulties [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RtI model is proposed as an alternative to the current model (Jiménez, 2017), under which the identification of students in need of a different instruction does not begin until at least two years of failure. The RtI model has shown promising results for improving students' reading achievement in the Canary Islands (Crespo et al, 2018). However, to implement the RtI model, it is necessary to develop universal screening measures that allow the early identification of students at risk of math failure.…”
Section: Introductionmentioning
confidence: 99%